(1.2) \( \lim _{x \rightarrow 1} \frac{\ln (-x+2)}{x-1} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To evaluate the limit \( \lim _{x \rightarrow 1} \frac{\ln (-x+2)}{x-1} \), we first substitute \( x = 1 \): \[ \frac{\ln(-1 + 2)}{1 - 1} = \frac{\ln(1)}{0} = \frac{0}{0} \] This indicates that we can apply L'Hôpital's Rule since both the numerator and the denominator approach 0. We need to differentiate the numerator and denominator separately. The derivative of the numerator, \( \ln(-x + 2) \), using the chain rule, is: \[ \frac{d}{dx} \ln(-x + 2) = \frac{1}{-x + 2} \cdot (-1) = \frac{-1}{-x + 2} = \frac{1}{x - 2} \] The derivative of the denominator \( x - 1 \) is: \[ \frac{d}{dx}(x - 1) = 1 \] Applying L'Hôpital's Rule gives us: \[ \lim_{x \rightarrow 1} \frac{\ln(-x + 2)}{x - 1} = \lim_{x \rightarrow 1} \frac{\frac{1}{x - 2}}{1} = \frac{1}{1 - 2} = \frac{1}{-1} = -1 \] Thus, the limit is \[ \boxed{-1} \]